Efficacy and Safety of Epratuzumab in Moderately to Severely Active Systemic Lupus Erythematosus: Results From Two Phase III Randomized, Double‐Blind, Placebo‐Controlled Trials. Issue 2 (28th January 2017) - Clowse, Megan E. B.; Wallace, Daniel J.; Furie, Richard A.; Petri, Michelle A.; Pike, Marilyn C.; Leszczyński, Piotr; Neuwelt, C. Michael; Hobbs, Kathryn; Keiserman, Mauro; Duca, Liliana; Kalunian, Kenneth C.; Galateanu, Catrinel; et al.
Abstract : Objective: Epratuzumab, a monoclonal antibody that targets CD22, modulates B cell signaling without substantial reductions in the number of B cells. The aim of this study was to report the results of 2 phase III multicenter randomized, double‐blind, placebo‐controlled trials, the EMBODY 1 and EMBODY 2 trials, assessing the efficacy and safety of epratuzumab in patients with moderately to severely active systemic lupus erythematosus (SLE). Methods: Patients met ≥4 of the American College of Rheumatology revised classification criteria for SLE, were positive for antinuclear antibodies and/or anti–double‐stranded DNA antibodies, had an SLE Disease Activity Index 2000 (SLEDAI‐2K) score of ≥6 (increased disease activity), had British Isles Lupus Assessment Group 2004 index (BILAG‐2004) scores of grade A (severe disease activity) in ≥1 body system or grade B (moderate disease activity) in ≥2 body systems (in the mucocutaneous, musculoskeletal, or cardiorespiratory domains), and were receiving standard therapy, including mandatory treatment with corticosteroids (5–60 mg/day). BILAG‐2004 grade A scores in the renal and central nervous system domains were excluded. Patients were randomized 1:1:1 to receive either placebo, epratuzumab 600 mg every week, or epratuzumab 1, 200 mg every other week, with infusions delivered for the first 4 weeks of each 12‐week dosing cycle, for 4 cycles. Patients across all 3 treatment groups also continued with their standard therapy. The primary end point was the response rate at week 48 according to the BILAG‐based Combined Lupus Assessment (BICLA) definition, requiring improvement in the BILAG‐2004 score, no worsening in the BILAG‐2004 score, SLEDAI‐2K score, or physician's global assessment of disease activity, and no disallowed changes in concomitant medications. Patients who discontinued the study medication were classified as nonresponders. Results: In the EMBODY 1 and EMBODY 2 trials of epratuzumab, 793 patients and 791 patients, respectively, were randomized, 786 (99.1%) and 788 (99.6%), respectively, received study medication, and 528 (66.6%) and 533 (67.4%), respectively, completed the study. There was no statistically significant difference in the primary end point between the groups, with the week 48 BICLA response rates being similar between the epratuzumab groups and the placebo group (response rates ranging from 33.5% to 39.8%). No new safety signals were identified. Conclusion: In patients with moderate or severely active SLE, treatment with epratuzumab + standard therapy did not result in improvements in response rates over that observed in the placebo + standard therapy group.